Study methodology and diabetes control in patients from the non‐English diabetes management project (NEDMP). (17th August 2016) - Dirani, Mohamed; Dang, Trung M; Xie, Jing; Gnanasekaran, Sivashanth; Nicolaou, Theona; Rees, Gwyneth; Fenwick, Eva; Lamoureux, Ecosse L
Abstract: Background: To describe the clinical characteristics of non–English speaking patients from the Diabetes Management Project (NEDMP), and compare their diabetes management and severity of diabetic retinopathy (DR) with the English‐speaking DMP sample (EDMP). Design: A prospective study was conducted on non‐English speaking adults with diabetes who attended the Royal Victorian Eye and Ear Hospital. Participants: 136 (90.1%) non‐English speaking adults were assessed, with a mean age of 72.2 years (range: 50‐88 years); 74 (54.4%) were male. Methods: Participants completed interviewer‐administered questionnaires and underwent visual acuity, fundus photography, optical coherence tomography, biochemistry and anthropometric measurements. The EDMP assessed 609 patients in 2009 using a similar protocol. Main Outcome Measures: Type and duration of diabetes, diabetes control and diabetic retinopathy. Results: A total of 127 (93.4%) and 8 (5.9%) participants reported having type 2 and type 1 diabetes, respectively, with a median (IQR) duration of 17 (14) years. The proportion of patients with poor diabetes control (HbA1c ≥ 7%) in the NEDMP was similar to the EDMP (64.0% and 68.2%, respectively; P  = 0.411). A significantly higher proportion of patients with DR in the NEDMP were found to have poor diabetes control (HbA1c ≥ 7%) compared to those without DR (80.9% vs. 50.0%, P  = 0.003). Almost two‐thirds of NEDMP patients (74/118) had DR and 23% (27/115) had diabetic macular edema. The prevalence of DR was similar between the NEDMP and EDMP studies, ranging from 25‐30% and 28‐29%. Conclusions: The clinical characteristics, diabetes control, and DR severity of English and non‐English‐speaking patients were similar. The high proportion of poor diabetes management in non‐English speaking patients with DR suggests educational and behavioural interventions to improve glycaemic control are warranted.